ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENAGIHAN PAJAK SECARA AKTIF TERHADAP PENCAIRAN TUNGGAKAN PAJAK (STUDI KASUS PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO) - Korua, Devika; Sabijono, Harijanto; Lambey, Robert (ACCOUNTABILITY, 2015)
Effective tax collection is an appropriate means to achieve the maximum tax revenue target. The goals of study is to determining the effectiveness and contribution of active tax billing actions which includes the warning leter, forced letter, and seizure letter to disbursement of tax arrears in Tax Office Pratama North Manado during 2013-2014. The type of research used in this study is a descriptive study with approach case study. Data collected through interviews and documentation. The results of the study indicate that the effectiveness of tax billing rate is still not effective and the contribution of active tax billing actions to disbursement of tax arrears is still lacking. The factors is a lack of public awareness, taxpayer compliance in paying his tax debt and less optimal active tax collection process.